Familial cerebral amyloidosis and spongiform encephalopathy. Issue 1 (January 1982) - Adam, J; Crow, T J; Duchen, L W; Scaravilli, F; Spokes, E
Abstract : Clinical and neuropathological investigations are presented of the "W" family in which there is a dominant inheritance of slowly progressive cerebellar ataxia and dementia. The disease is of insidious onset and its average duration more than 4 years. Pathological findings included amyloid deposition in cerebellar and cerebral tissue; vascular amyloid in one case; and spongiform encephalopathy and astrocytic hyperplasia typical of Creutzfeldt-Jakob disease. Neuritic plaques of the senile (Alzheimer) type were present to a lesser extent. This study confirms the familial association between cerebral amyloidosis and spongiform encephalopathy.